2016
DOI: 10.1002/glia.22958
|View full text |Cite
|
Sign up to set email alerts
|

miR‐124‐9‐9* potentiates Ascl1‐induced reprogramming of cultured Müller glia

Abstract: The Müller glia of fish provide a source for neuronal regeneration after injury, but they do not do so in mammals. We previously showed that lentiviral gene transfer of the transcription factor Achaete-scute homolog 1 (Ascl1/Mash1) in murine Müller glia cultures resulted in partial reprogramming of the cells to retinal progenitors. The microRNAs (miRNAs) miR-124-9-9* facilitate neuronal reprogramming of fibroblasts, but their role in glia reprogramming has not been reported. The aim of this study was to test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 80 publications
6
67
0
Order By: Relevance
“…Thus, the temporal expression profile of cell‐cycle regulators indicated cell‐cycle re‐entry and proliferation upon retinal explantation, followed by cell‐cycle inhibition and exit recapitulating the timing of MG proliferation and derived progeny differentiation observed by cell tracking and transgenic lineage tracing (Figure b,c and Löffler et al, ; Ueki et al, ). Further, Ascl1 is required to stimulate retinal regeneration in zebrafish (Fausett, Gumerson, & Goldman, ; Ramachandran, Fausett, & Goldman, ; Ramachandran et al, ; Wan et al, ), is sufficient to reprogram MG to a neurogenic state (Pollak et al, ; Ueki et al, ; Wohl & Reh, ), and is a master regulator gene of retinal stem cells, along with Vsx2 and the neurogenic transcription factors Neurog2 and Notch signaling. Previous studies have shown that MG could be stimulated to endogenously express Ascl1, Neurog2, and Vsx2 at the protein level (Löffler et al, ; Nelson et al, ), which we determined here in isolated and enriched MG at the molecular level.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the temporal expression profile of cell‐cycle regulators indicated cell‐cycle re‐entry and proliferation upon retinal explantation, followed by cell‐cycle inhibition and exit recapitulating the timing of MG proliferation and derived progeny differentiation observed by cell tracking and transgenic lineage tracing (Figure b,c and Löffler et al, ; Ueki et al, ). Further, Ascl1 is required to stimulate retinal regeneration in zebrafish (Fausett, Gumerson, & Goldman, ; Ramachandran, Fausett, & Goldman, ; Ramachandran et al, ; Wan et al, ), is sufficient to reprogram MG to a neurogenic state (Pollak et al, ; Ueki et al, ; Wohl & Reh, ), and is a master regulator gene of retinal stem cells, along with Vsx2 and the neurogenic transcription factors Neurog2 and Notch signaling. Previous studies have shown that MG could be stimulated to endogenously express Ascl1, Neurog2, and Vsx2 at the protein level (Löffler et al, ; Nelson et al, ), which we determined here in isolated and enriched MG at the molecular level.…”
Section: Resultsmentioning
confidence: 99%
“…The forced expression of miR124 and another neuron-specific microRNA, miR9/9*, is sufficient for the cells converted from adult fibroblasts to adopt neuronal features [14]. In line with this, it was shown that the combination of miR9/9* and miR124 can accelerate neuronal conversion [23,24]. The effect of short hairpin-mediated knockdown of REST (RESTi) on neuronal conversion efficiency is mediated at least in part via the upregulation of miR9 and miR124 as an effect of RESTi, but it is becoming clear that RESTi also acts via microRNA-independent pathways [22].…”
mentioning
confidence: 71%
“…Cluster analysis of these data revealed subgroups of miRNAs that showed defined temporal expression profiles. They included, for example, members of the let‐7 family or miR‐124, known to be involved in retinal cell maturation and Müller glia reprogramming (Quintero, Gómez‐Montalvo, & Lamas, ; Wohl & Reh, ; Xia & Ahmad, ) and miR‐17, ‐106, reported to be key regulators of the neurogenic‐to‐gliogenic transition in neural progenitor cells (Naka‐Kaneda et al, ). A specific cluster (C2) that included miR‐29a, ‐29b, ‐29c, ‐143, ‐129‐3p underwent a dramatic decrease of expression as retinal development proceeded (Hackler et al, ).…”
Section: Mirnas In Retinal Development and Müller Glia Differentiationmentioning
confidence: 99%
“…Hence, there is evidence that ectopically expressed miR-124, the most abundantly expressed miRNA in neuronal cells (Cheng, Pastrana, Tavazoie, & Doetsch, 2009), induces murine MGDPs to acquire an early neuronal (b-III tubulin-expressing) phenotype (Quintero et al, 2016). Moreover, lentiviral gene transfer-mediated overexpression of miR-124, -9, and -9* leads to upregulation of retinal progenitor genes (Ascl1 and Hes5) and neuronal genes (Neurofilament-M, doublecortin, MAP2, and TUJ1) in PN12 cultured M€ uller glia (Wohl & Reh, 2016b) (Figure 3). The authors also demonstrate that overexpression of miR-124-9-9* enhances the ascl1-mediated reprogramming of M€ uller glia to neurons (Wohl & Reh, 2016b).…”
Section: Re Ti N a L R Eg En E Ra Ti On : M € Ul L E R Gl I A De -Dmentioning
confidence: 99%